Thermoluminescence properties of Li2B4O7:Cu, B phosphor synthesized using solution combustion technique. (December 2017) - Ozdemir, A.; Altunal, V.; Kurt, K.; Depci, T.; Yu, Y.; Lawrence, Y.; Nur, N.; Guckan, V.; Yegingil, Z.
Abstract: To determine the effects of various concentrations of the activators copper (Cu) and boron (B) on the thermoluminescence (TL) properties of lithium tetraborate, the phosphor was first synthesized and doped with five different concentrations of copper (0.1–0.005 wt%) using solution combustion method. 0.01 wt% Cu was the concentration which showed the most significant increase in the sensitivity of the phosphor. The second sort of Li2 B4 O7 :Cu material was prepared by adding B (0.001–0.03 wt%) to it. The newly developed copper-boron activated lithium tetraborate (Li2 B4 O7 :Cu, B) material with 0.01 wt% Cu and 0.001 wt% B impurity concentrations was shown to have promise as a TL phosphor. The material formation was examined using powder x-Ray Diffraction (XRD) analysis and Scanning Electron Microscope (SEM) imaging. Fourier Transform Infrared (FT-IR) spectrum of the synthesized polycrystalline powder sample was also recorded. The TL glow curves were analyzed to determine various dosimetric characteristics of the synthesized luminophosphors. The dose response increased in a "linear" way with the beta-ray exposure between 0.1–20 Gy, a dose range being interested in medical dosimetry. The response with changing photon and electron energy was studied. The rate of decay of the TL signal was investigated both for dark storage and under direct sunlight. Li2 B4 O7 :Cu, B showed no individual variation of response in 9 recycling measurements. The fluorescence spectrum was determined. The kinetic parameters were estimated by different methods and the results discussed. The studied properties of synthesized Li2 B4 O7 :Cu, B were found all favorable for dosimetric purposes. Highlights: Li2 B4 O7 :Cu, B synthesis using solution combustion method with various concentrations. Structure analysis of Li2 B4 O7 :Cu, B using XRD, SEM and FTIR methods. Investigation of thermoluminescent properties of Li2 B4 O7 :Cu, B. Relatively good energy independence and linear dose response up to 20 Gy. Kinetic parameters were evaluated by various heating rates; Initial Rise; CGCD methods.